Innovative health tracker that provides advanced functionalities to support and guide users in modifying their lifestyle: a Straussian ground theory approach - Uher, Ivan; Vašková, Hedviga; Poráčová, Janka; Cimbolákova, Iveta; Küchelová, Zuzana; Buková, Alexandra; Bernasovská, Jarmila (Frontiers in Psychology, 2024)
Objective: Health can be described as homeostasis and optimal functioning across various biopsycho-social dimensions and processes, allowing an individual to adapt and respond effectively to extrinsic and intrinsic challenges. Where our thoughts, choices, behaviors, experiences and feelings shape our existence. By transitioning from unconscious reactions to conscious responses, we can establish novel habits and behavior, actively embracing positive shifts in our lifestyle.The presented examination focuses on the Smartwatch (SW), analyzing the incorporation of potentially progressive attributes that could enrich our lifestyle pursuits. The objective is not the health disorders themselves but the employment of wearable devices to create a strong sense of coherence in the Straussian grounded theory approach. The study had no subjects.Results: The potential of the SW has been partially explored in lifestyle intervention, modification, research, and practice.Conclusions: Based on our examination, creating an innovative SW capable of aiding individuals in better comprehending their behaviors and motivating them toward comprehensive changes in their lifestyle is a challenging yet attainable endeavor. Our ambition is to bring into existence SW capable of comprehensively measuring and evaluating Interoception, Circadian rhythm, selected Lifestyle pillars, and their associated components, seamlessly, comprehensively integrating them into current SW features. It focuses on boosting motivation, maintenance, and amelioration regarding one's lifestyle. The novel approach strives to boost both immediate and underlying factors that actively contribute to improving one's metacognition.